Framework para apoio à tomada de decisão na aquisição de equipamentos industriais garantindo transferência de conhecimento e tecnologia - Tomelin, Janete von Zeschau (2018)
This research aimed to develop a framework to support the search for excellence on Knowledge and Technology Transfer on new equipment acquisition by the industrial sector. The methodology is a bibliographic research, applied from nature, a qualitative approach, with descriptive objectives and bibliographic documentary. To be guided on the decision-making situations, industries need a tool which points to successive paths based on previous successes, variables theoretically referenced, as well as alerts for deviations and barriers. This way this study defined dimensions and variables which need to be considered at the decision making moment of the industrial equipment acquisition. The tool is a framework and questioner composed by 25 questions to be answered before making the decision that results on the Knowledge and Technology Transfer Octagon for the industrial sector. The Knowledge and Technology Transfer Octagon can be applied together with budgeting to clarify the largest number of doubts about the equipment, as well as to be used by equipment suppliers to provide the recipients with information that are important for a successful Knowledge/Technology Transfer.